Nghiên cứu tính chất cơ lý và cấu trúc vật liệu compozit nhựa nên polypylen và hạt gypsum biến tính natri dodecyl sunphat - Giang, Nguyễn Vũ; Trung, Đỗ Quang; Trung, Trần Hữu; Huynh, Mai Đức; Minh, Nguyễn Quang (Vietnam Journal of Chemistry, 2014)
In this study, the composite materials based on polypropylene (PP) and waste gypsum (Gyp) was prepared by melt mixing method in a Haake mixer (Germany). Original Gyp (OGyp) was modified by surfactant as sodium dodecyl sulfate (SDS) (abbreviated as MGyp). Analysis of Fourrier transform infrared spectroscopy (FT-IR) demonstrated that the SDS was grafted onto the surface of Gyp particles. Besides, the results of thermogravimetric analysis (TGA) revealed the decomposition peak of SDS at the temperature around 580-660 oC. Melt rheological properties of composite materials showed the increase in the relative viscosity of the modified Gyp composite. In other hand, investigatation of mechanical properties of composites also showed that the MGyp increased the tensile strength and Young’s modulus of PP/MGyp up to 8.23 % and 43.78 % in comparison with the pure PP, respectively.  Field emission scanning electron microscopy (FESEM) images desmontrated the dispersibility of MGyp on PP matrix was better than that of the Ogyp. Keywords: Gypsum, polypropylene, sodium dodecyl sunfate, polymer composite, mechanical properties.